Pt(II)-Bisacetylide ‘Roller Wheels’: Molecular Engineering towards Small Bandgap, High Crystallinity, and Controlled Triplet Exciton Processes - Qin, Yang (Synlett, 2023)
Triplet excitons are ubiquitous in organic chromophores and possess intrinsically longer lifetimes than their singlet exciton counterparts, and thus potentially larger diffusion lengths that have been considered beneficial for organic solar cells (OSCs). However, existing triplet-generating materials rarely possess low bandgap, high triplet energy and yield, and good crystallinity and charge mobility within a single compound. In this Account, I first describe the rationales behind our ‘roller-wheel’-type molecular structural designs through a brief literature survey and our initial attempt in Pt-containing conjugated polymers. Then, a series of novel Pt-bisacetylide-containing small molecules will be discussed. I mainly focus on the thought process for selecting the building blocks and detail their synthetic strategies, as well as their solid-state structures, especially that of the single crystals, confirming the effectiveness of our structural designs. Next, photophysical properties of these compounds are discussed in the context of optical spectroscopy and transient absorption spectroscopy, which is corroborated by theoretical calculations. Organic solar cells employing these compounds are introduced next, one of which displayed record-setting performance among Pt-containing materials. I end this Account with an outlook on future works with a focus on molecular engineering to control triplet excited-state energetics and dynamics.1 Introduction2 Initial Attempt3 Rationale of Design4 Synthesis of ‘Roller Wheels’5 Solid-State Structures of ‘Roller Wheels’6 Photophysical Studies7 Theoretical Investigation8 Device Application9 Outlook – Managing Triplet Excited States
Keywords: Pt-bisacetylide; triplet excited state; organic solar cell; crystallinity; conjugated molecules; conjugated polymers